Distribution of poverty and inequality indices for various groups in Greece using the bootstrap technique - Dimitra Aggelopoulou; Stavros Zografakis; Panayiotis Sypsas (International Journal of Economic Sciences and Applied Research, 2011)
The present work estimates poverty and inequality indices in various groups that are known to have high contributions to poverty and inequality, such as farmers, pensioners and families with 3 or more children. Using the bootstrap technique, we estimate confidence intervals for these indices and examine if the decrease of poverty and inequality during the years 1998/99 and 2004/05 in these groups is statistically significant or within the boundary of the confidence interval. For the purpose of the study, we use household income data from the last two Household Budget Surveys (HBS) which cover the entire population of Greece conducted in 1998/99 and 2004/05 by the National Statistical Service of Greece (NSSG). In regard to the methodological issues, we chose the individual as the unit of analysis and the family equivalence scales used by Eurostat.
Keywords: D31; I32; 330; poverty; inequality